2014
DOI: 10.1039/c3tc32376e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electron transfer in the nanocomposite of the graphene oxide–Au nanocluster with graphene oxide as a donor

Abstract: Novel electron transfer results in PL quenching in both graphene oxide–Au25 and graphene oxide–Au10 nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 59 publications
3
56
0
Order By: Relevance
“…Kogo determined the HOMO and LUMO potentials of GSH-AuNCs by photoelectrochemical analysis (Kogo et al, 2010(Kogo et al, , 2012Sakai and Tatsuma, 2010). Wen confirmed the band gap of BSA-AuNCs again by studying the electron transfers between AuNCs and GO (Wen et al, 2014). The LUMO and HOMO positions of different AuNCs can be deduced based on the results of these studies.…”
Section: Photoelectrochemical Properties Of Auncs/sam/au Sensorsmentioning
confidence: 63%
See 1 more Smart Citation
“…Kogo determined the HOMO and LUMO potentials of GSH-AuNCs by photoelectrochemical analysis (Kogo et al, 2010(Kogo et al, , 2012Sakai and Tatsuma, 2010). Wen confirmed the band gap of BSA-AuNCs again by studying the electron transfers between AuNCs and GO (Wen et al, 2014). The LUMO and HOMO positions of different AuNCs can be deduced based on the results of these studies.…”
Section: Photoelectrochemical Properties Of Auncs/sam/au Sensorsmentioning
confidence: 63%
“…Each BSA-AuNC, DHLA-AuNC GSH-AuNC and MUA-AuNC contained 25, 28, 15 and 10 Au atoms, respectively. Based on the band gap results obtained for nanoclusters composed of different numbers of atoms (Wen et al, 2014), potentials of À 500 mV to 500 mV, at which the Fermi level is between each HOMO and LUMO, were applied in all measurements to maintain a stable photocurrent and allow for suitable comparison.…”
Section: Photoelectrochemical Properties Of Auncs/sam/au Sensorsmentioning
confidence: 99%
“…Time-resolved PL is an effective technique to analyze the structural changes via investigation of the fluorescence quenching, as reported in our previous work [32][33][34]. Hedley et al [6] reported that no PTB7 fluorescence is observed even at a timescale as short as 2 ps with a selective excitation wavelength of 670 nm.…”
Section: Resultsmentioning
confidence: 95%
“…Currently, various types of nanomaterials have been employed to provide fluorescence response and construct ultrasensitive biosensors with the development of nanoscience and nanotechnology (Min et al, 2011;Zhang, 2012). Fluorescent nanomaterials, especially quantum dots (QDs) and noble metal nanoclusters (NCs), have been appearing as powerful and sensitive probes and attracted numerous attentions (Yang and Lian, 2014;Wen et al, 2014). Likewise, carbon dots (CDs) appear as a new class of 'zero-dimensional' fluorescent nanomaterials in the carbon family (Baker and Baker, 2010), and exhibit enormous prospects across the scientific disciplines owing to their ease of synthesis, abundance of raw material in nature, excellent chemical and colloidal stability, low photobleaching, scarcely optical blinking, favorable biocompatibility and superior water dispersibility (Hola et al, 2014;Song et al, 2014;Yang et al, 2013;Dong et al, 2012;Song et al, 2012).…”
Section: Introductionmentioning
confidence: 99%